2023
DOI: 10.7150/ijbs.86492
|View full text |Cite
|
Sign up to set email alerts
|

The PTGS2/COX2-PGE2 signaling cascade in inflammation: Pro or anti? A case study with type 1 diabetes mellitus

Abstract: Prostaglandins are lipid mediators involved in physiological processes, such as constriction or dilation of blood vessels, but also pathophysiological processes, which include inflammation, pain and fever. They are produced by almost all cell types in the organism by activation of Prostaglandin endoperoxide synthases/Cyclooxygenases. The inducible Prostaglandin Endoperoxide Synthase 2/Cyclooxygenase 2 (PTGS2/COX2) plays an important role in pathologies associated with inflammatory signaling. The main product d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…This is evidenced by the activation of key molecular pathways inducing tolerance, such as OXPHOS, PPAR signalling, lysosome, and phagosome, as well as a specific subset of tolerogenic-associated genes, including PTGS2. Previously, we demonstrated that PTGS2 and its product, prostaglandin E 2, endow a tolerogenic phenotype to DCs after efferocytosis and prevent cytokine-induced apoptosis in BL001-treated islet β-cell 22,23,82 . Consistent with a shift towards a tolerogenic phenotype, levels of several cell surface markers associated with mDCs (CXCR4 and CD54) were decreased, as did the secretion of IL-7 in cells treated with BL001.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…This is evidenced by the activation of key molecular pathways inducing tolerance, such as OXPHOS, PPAR signalling, lysosome, and phagosome, as well as a specific subset of tolerogenic-associated genes, including PTGS2. Previously, we demonstrated that PTGS2 and its product, prostaglandin E 2, endow a tolerogenic phenotype to DCs after efferocytosis and prevent cytokine-induced apoptosis in BL001-treated islet β-cell 22,23,82 . Consistent with a shift towards a tolerogenic phenotype, levels of several cell surface markers associated with mDCs (CXCR4 and CD54) were decreased, as did the secretion of IL-7 in cells treated with BL001.…”
Section: Discussionmentioning
confidence: 95%
“…Nonetheless, these approaches have yet to reach ethical approval for clinical trials. Pharmacological activation of LRH-1/NR5A2 could circumvent these caveats encountered by cell therapy by attenuating the pro-inflammatory environment-without suppressing the general immune system-while increasing β-cell survival and performance 22,23 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations